Intra-Campaign Changes in Voting Preferences: The Impact of Media and Party Communication. (3rd April 2018) - Johann, David; Königslöw, Katharina Kleinen-von; Kritzinger, Sylvia; Thomas, Kathrin
Abstract : An increasing number of citizens change and adapt their party preferences during the electoral campaign. We analyze which short-term factors explain intra-campaign changes in voting preferences, focusing on the visibility and tone of news media reporting and party canvassing. Our analyses rely on an integrative data approach, linking data from media content analysis to public opinion data. This enables us to investigate the relative impact of news media reporting as well as party communication. Inherently, we overcome previously identified methodological problems in the study of communication effects on voting behavior. Our findings reveal that campaigns matter: Especially interpersonal party canvassing increases voters' likelihood to change their voting preferences in favor of the respective party, whereas media effects are limited to quality news outlets and depend on individual voters' party ambivalence.